Hardware Conceptual Design of Tsunhan-14 Multimodal Robot Observer in Support of TNI Tasks - Trisno Iswandi; Erzi Aqson Gani; Yohanes Kurnia.W; Hendrana Tjahjadi (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
The development of technology in the military field has changed from time to time. This dynamic must be taken seriously because they are a challenge, and pose a potential threat to the sovereignty of the Unitary State of the Republic of Indonesia (NKRI), As well as the trend of the technology-based warfare today. So it has become a necessity for the Indonesian National Army (TNI) to accept it. One of the popular technologies today, war robt technology(warbo), and including multimodal robots with a variety of basic missions. Furthermore, developing a multimodal robot concept design that can fulfil TNI surveillance needs. The methodology used is in the form of interview, observations, comparison, and literature studies by applying system engineering theory and life cycle models. This research has successfully formulated user requirement objectivies which are then elaborated into robot design concepts including characteristic design, and architecture design of multimodal monitoring robots. The hardware on the robot is design differently from others because it has the ability to fly and walk on the ground. The robot is also conceptualised to have advantages in terms of durability with agility, silence, and operate with various terrain conditions. Equipped with sensors to see, hear, measure ambient temperature, and read surrounding conditions using camera sensors, where the robot moves autonomously equipped with GPS and Lidar can send data in the form of audio visual directly to the Ground Control System (command centre). The concept design of the multimodal monitoring robot called Tsunhan-14 is expected to be the basis for determining technical requirement and further developed into a national innovation that is utilized as part of the TNI’s war strategy.